2020
DOI: 10.1016/j.vetmic.2019.108513
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, antigenic and pathogenic characterization of avian coronaviruses isolated from pheasants (Phasianus colchicus) in China

Abstract: A B S T R A C TTwo viruses were isolated in 2017 from commercial pheasants with severe clinical signs and mortality in Shandong and Anhui provinces, China, respectively. We examined the pathogenic effects of the viruses in chicken embryos and the size and morphology of the virus particles, performed phylogenetic analysis based on the S1 gene and complete genomic sequences, and examined the antibody responses against infectious bronchitis virus (IBV). The results suggested that the viruses I0623/17 and I0710/17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Once the binding occurs, conformational changes in the S protein, like pH reducing and/or S protein proteolysis, promote splitting of S1 from S2. Consequently, membrane fusion is placed by the S2 region ( Han et al, 2020 ). S2 subunit has two heptad repeat (HR) domains, (HR1) and (HR2), that interact together to form a six-helix bundle (6-HB) fusion core to approximate the viral and cellular interaction ( Xia et al, 2020 ).…”
Section: Mechanism Of Sars-cov-2 Genome Replication and Translationmentioning
confidence: 99%
“…Once the binding occurs, conformational changes in the S protein, like pH reducing and/or S protein proteolysis, promote splitting of S1 from S2. Consequently, membrane fusion is placed by the S2 region ( Han et al, 2020 ). S2 subunit has two heptad repeat (HR) domains, (HR1) and (HR2), that interact together to form a six-helix bundle (6-HB) fusion core to approximate the viral and cellular interaction ( Xia et al, 2020 ).…”
Section: Mechanism Of Sars-cov-2 Genome Replication and Translationmentioning
confidence: 99%
“…PhCoVs belong to the genus Gammacoronavirus and subgenus Igacovirus [ 233 , 235 ] and have a high degree of genetic similarity with chicken and turkey CoVs [ 258 , 259 , 260 , 261 ]. Han and collaborators reported different evolution patterns and tissue tropisms between different PhCoVs [ 262 ]. Cavanagh and collaborators confirmed that CoVs that naturally infect pheasants are genetically similar to IBV, but they do not cause disease when inoculated experimentally in chickens, even if antibodies are produced [ 243 , 258 , 260 ].…”
Section: Coronavirus Diseases In Animalsmentioning
confidence: 99%
“…Cavanagh and collaborators confirmed that CoVs that naturally infect pheasants are genetically similar to IBV, but they do not cause disease when inoculated experimentally in chickens, even if antibodies are produced [ 243 , 258 , 260 ]. Additional studies of the complete genomic sequence are necessary to better understand the relation between the pathogenicity of IBVs in pheasants and clarify the link between PhCoVs and IBVs [ 262 ]. Outbreaks associated with CoVs infection in pheasants were reported for the first time in the 1980s.…”
Section: Coronavirus Diseases In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…IBV is associated with a high frequency of point mutations, insertions, deletions, and recombination [ 1 , 6 ]. Currently, IBV is comprised of seven genotypes that together include 36 distinct viral lineages and several unique variants [ 7 , 8 , 9 ]. Among these genotypes, GI-19 (also called QX-like) has expanded globally in recent years [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%